2020
DOI: 10.1097/rlu.0000000000003469
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT in Anti–Leucine-Rich Glioma-Inactivated 1 Antibody Encephalitis

Abstract: We report the case of a 55-year-old man presenting pseudopsychiatric behavior disorders of subacute-onset. MRI showed a FLAIR (fluid-attenuated inversion recovery) hyperintensity in the left hippocampus. The diagnosis of limbic encephalitis was raised, and the patient was referred for an 18F-FDG PET/CT. PET/CT depicted an increased uptake of the left mesiotemporal structures and also an increased uptake of both cerebellum and striatal areas. This pattern was compatible with an anti–leucine-rich glioma-inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…2 , Abb. 3 ) 47 48 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 . Dabei kann sowohl ein Hyper-, seltener auch ein Hypometabolismus mesiotemporal auftreten 76 77 81 .…”
Section: Zerebrale Fdg-petunclassified
“…2 , Abb. 3 ) 47 48 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 . Dabei kann sowohl ein Hyper-, seltener auch ein Hypometabolismus mesiotemporal auftreten 76 77 81 .…”
Section: Zerebrale Fdg-petunclassified
“…Brain 18 F-FDG-PET imaging reports uncovered abnormal metabolic patterns of anti-VGKC encephalitis, which may be symptom-specific. [14][15][16][17] In the total of 34 patients, basal ganglia hypermetabolism was observed in 28 subjects (82%), and 68% of patients showed medial temporal lobe (MTL) hypermetabolism, the pattern of which appeared earlier than in MRI. It has also been reported that isolated basal ganglia hypermetabolism was more frequently observed in subjects with FBDS (Figures 1 and 2).…”
Section: Anti-voltage-gated Potassium Channel Encephalitismentioning
confidence: 99%
“…2, Abb. 3) [47,48,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80]. Dabei kann sowohl ein Hyper-, seltener auch ein Hypometabolismus mesiotemporal auftreten [76,77,81].…”
Section: Zerebrale Fdg-petunclassified